Duration of Use of Computer as Risk Factor for Developing Back Pain among Indian Office Going Women - Varte, Lalhmunlien Robert; Rawat, Shweta; Singh, Inderjeet; Majumdar, Dhurjati (Asian Journal of Medical Sciences, 2013)
Introduction: The study was designed to investigate back pain among working women in one of the largest Research and Development Organization in India and identify occupational factors associated with lower back pain by means of a survey of female employees. Methods: This study investigated the relative risk of whether different age groups, job types, body mass index (BMI), years or service, screen viewing distance, self perception of comfort level and duration of use of computer have a bearing on the occurrence of back pain and if such risk factors aggravate cases of back pain. Results: In the unadjusted table, there was a statistically significant chance of developing backpain as the age increases (odds ratio) OR 1.56, 95% (confidence interval) CI (1.030 - 2.372), however, after adjusting for the other co-variates, this chance was not of significance. Job types, body mass index (BMI) >30 (OR >1 (0.802-1.877), years of service and screen distance OR >1 (0.96-1.745) all showed a positive association with back pain though the p values were not of statistically significance. In the adjusted table, for those who use the computer daily at the workplace for more than 6 hours, there was a statistically significant association for this group of developing back pain as compared to the first group i.e. those who work for 0-2 hours, as shown by OR 1.79, (1.123 - 2.864). Conclusion: The present study indicated that backpain is present in as much as about 25.3% of the study population. For those who use the computer >6 hours daily, there was a statistically significant chance of developing backpain. DOI: http://dx.doi.org/10.3126/ajms.v3i1.5567 Asian Journal of Medical Sciences 3(2012) 6-12